Girls, Homelessness, and COVID-19: The Urgent Need for Research and Action. Issue 3 (1st December 2020) - Schwan, Kaitlin; Dej, Erin; Versteegh, Alicia
Abstract: Equitable access to adequate housing has increasingly been recognized as a matter of life and death during the COVID-19 pandemic. Despite this, there has been limited gendered analysis of how COVID-19 has shaped girls' access to housing. In this article we analyze how the socio-economic exclusion of girls who are homeless is likely to increase during the COVID-19 pandemic in Canada. We suggest that three structural inequities will deepen this exclusion: the disproportionate burden of poverty faced by women; the inequitible childcare responsibilities women bear; and the proliferation of violence against women. We argue for the development of a research agenda that can address the structural conditions that foster pathways into homelessness for low-income and marginalized girls in the context of COVID-19 and beyond.